Harnessing Artificial Intelligence for Effective Corporate Governance: Evaluating the Board of Directors Role and Its Influence on Individual Investors and ESG Practices - Swathi G. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
As the landscape of corporate governance undergoes a transformative shift in the digital age, this research paper investigates the integration of Artificial Intelligence (AI) tools into governance frameworks. Focusing on the pivotal role of the Board of Directors, the study delves into the multifaceted impact of AI on corporate decision-making processes. Concurrently, it explores the intricate relationship between corporate governance, individual investors, and Environmental, Social, and Governance (ESG) practices. The primary objectives are to assess the evolving responsibilities of the Board, analyze the deployment of AI tools in governance structures, and understand their collective influence on the awareness levels of individual investors regarding ESG considerations. The literature review navigates through traditional and contemporary corporate governance models, elucidating the role of the Board of Directors and the dynamic integration of AI. Drawing upon theoretical frameworks such as agency theory, stakeholder theory, and behavioral finance, the paper establishes a conceptual foundation for the ensuing empirical investigation. Methodologically, the research employs a comprehensive approach, encompassing sample selection, data collection methods, and analytical techniques to scrutinize the intricate interplay of AI, boards, and investors. The subsequent sections delineate the historical evolution of the Board’s responsibilities, shedding light on the challenges and opportunities presented in the digital era. Simultaneously, an in-depth analysis of AI applications in corporate governance, including case studies and ethical considerations, provides a nuanced perspective. Individual investors’ perceptions of ESG factors are scrutinized, emphasizing the impact of corporate governance on investor trust. The research concludes with a synthesized exploration of the interdependencies between AI, the Board of Directors, and individual investors, offering insights into the transformative potential of AI in enhancing corporate governance practices. The study contributes to the existing literature by unraveling the challenges, risks, and future implications associated with this paradigm shift. Recommendations for future research and practical implications provide a roadmap for stakeholders navigating the dynamic intersection of AI, corporate governance, and investor relations.